2012
DOI: 10.1128/aem.00351-12
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Grouping and Virulence Potential of Extended-Spectrum-β-Lactamase-Producing Escherichia coli Strains in Cattle

Abstract: ABSTRACTIn line with recent reports of extended-spectrum beta-lactamases (ESBLs) inEscherichia coliisolates of highly virulent serotypes, such as O104:H4, we investigated the distribution of phylogroups (A, B1, B2, D) and virulence factor (VF)-encoding genes in 204 ESBL-producingE. coliisolates from diarrheic cattle. ESBL genes, VFs, and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 43 publications
7
22
2
Order By: Relevance
“…A low prevalence (2/205 isolates, 0.97%) of ESBL-producing E. coli was found only in the cow samples which belonged to the phylogenetic group A and phylogenetic subgroup A1. Our results were in accordance with the results of Valat et al 45 who reported that ESBL-producing E. coli isolates from cattle belonged mainly to the phylogroup A. The low prevalence of ESBLproducing E. coli was similar to the results of Shiraki et al, 46 but it was very lower than that of some previous studies.…”
Section: Discussionsupporting
confidence: 70%
“…A low prevalence (2/205 isolates, 0.97%) of ESBL-producing E. coli was found only in the cow samples which belonged to the phylogenetic group A and phylogenetic subgroup A1. Our results were in accordance with the results of Valat et al 45 who reported that ESBL-producing E. coli isolates from cattle belonged mainly to the phylogroup A. The low prevalence of ESBLproducing E. coli was similar to the results of Shiraki et al, 46 but it was very lower than that of some previous studies.…”
Section: Discussionsupporting
confidence: 70%
“…The association between some phylogroups and antimicrobial resistance patterns is for now poorly understood. Nevertheless, several studies have already highlighted that phylogroup A E. coli are over‐represented within resistant strains isolated in France (Smati et al., 2013), including chromosomal AmpC β‐lactamase overproducers carried by humans (Corvec et al., 2007) as well as ESBL E. coli detected in cattle (Valat et al., 2012) and ampicillin‐resistant isolates from pigs (Bibbal, Dupouy, Prère, Toutain, & Bousquet‐Mélou, 2009). Further studies are still needed to determine if E. coli belonging to phylogroup A are more likely to acquire antimicrobial resistances and why.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the E. coli isolates had untypeable O and H antigens (OUT, HUT). Neither E. coli clone ST131 (O25:H4) nor enterohemorrhagic E. coli O157, O26, or O111 or other serotypes commonly isolated from human infections (8) were detected from the 13 isolates.…”
Section: Fig 2 Pfge Patterns and Cluster Analysis Of 13 Ctx-m-producimentioning
confidence: 99%
“…ince 2000, Escherichia coli and other Enterobacteriaceae species producing CTX-M-type extended-spectrum ␤-lactamases (ESBLs) (CTX-M) have been commonly isolated from community-acquired extraintestinal infections in humans and their companion animals (1, 2, 3, 4), from food-producing animals (3,5,6,7,8), and from retail meats, including chicken, beef, and pork (3), worldwide. The CTX-M-type genes are assumed to have been transferred separately to plasmids, including complex class 1 integrons and transposons (9), from chromosomes of different Kluyvera species (i.e., Kluyvera ascorbata, K. georgiana, and K. cryocrescens) that live in water, soil, and human and animal intestinal tracts; therefore, CTX-M has been divided into five clusters (CTX-M-1, CTX-M-2, CTX-M-8, CTX-M-9, and CTX-M-25) from base sequence homology (1, 9).…”
mentioning
confidence: 99%